A Model Experiment Design Using the Taguchi Method: A Case Study Of Making Concrete Roof - Idris Nur Permadi; Dini Basiratun Nisa (Jurnal Riset Ilmu Teknik, 2023)
This research was conducted at a company manufacturing paving blocks, ceramics, ventilation, concrete, and roof tiles. This study aims to improve the quality of concrete tile products, which experience the most cracks and breaks. Research to determine the composition of concrete roof tiles can be carried out by design experiments using the Taguchi method. This experiment used raw materials such as cement, sand, milled flour, and water. The concluding results show that the quality of concrete roof tiles is based on the results of the Taguchi method and confirmation experiments which are characterized by an increase in the compressive strength of the concrete tile based on the average value (μ) and its variability (SNR). The average compressive strength (µ) of concrete roof tiles increased from 19,814 ≤ 21,208 ≤ 22,602 in the Taguchi experiment to 26,406 ≤ µconfirmation ≤ 29,894 in the confirmation experiment. While the variability (SNR) increased from 25.532 ≤ 27.521 ≤ 29.510 in the Taguchi experiment to 26.473 ≤ S/N confirmed ≤ 31.469 in the confirmation experiment. The optimal composition of cement, sand, milled flour, and water that produces the best compressive strength based on the response factor and SNR is 0.9 kg: 0.5 kg: 0.4 kg: 0.3 kg, respectively. The most influential factors on the compressive strength of concrete roof tiles are the amount of sand and the number of flour mills